To What Extent Has Artificial Intelligence Impacted EFL Teaching and Learning? A Systematic Review - Al-Raimi, Mohammed; Mudhsh, Badri Abdulhakim; Muqaibal, Muna Hussain; Al-Yafaei, Yasir (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
Utilizing artificial intelligence (AI) technologies in EFL teaching and learning has brought about unimaginable opportunities to enhance learners’ fluency and proficiency in the target language as it is evident that employing AI tools helps learners develop their language skills, enhance engagement and motivation, ease foreign language anxiety, and ultimately acquire the target language. This meta-analysis aims to find out to what extent AI has impacted EFL teaching and learning by providing a systematic review of research papers published from 2020 to 2023. The review concentrated on four areas of EFL contexts: AI in EFL contexts, learners’ and teachers’ perceptions of AI tools, EFL learners’ motivations and engagements towards AI tools, and the integration of AI tools in language skills. The automated model developed by Guan et al.’s (2020) to collect published work from numerous databases such as Scopus, Web of Science, ERIC, Semantic Scholar, and Google Scholar was adopted. Findings of this review exhibit that employing AI technologies in the EFL settings has significantly benefitted the process of teaching and learning resulting in the mastery of the productive skills on the part of learners. On the other hand, the review shows there is a current lack of research related to receptive skills. As far as the learners’ and teachers’ perspectives regarding the integration of AI tools are concerned, the review voiced favourable perceptions concerning utilizing AI tools; however, the pedagogical implications of utilizing AI tools from the teachers’ point of view have been insufficiently addressed by research conducted so far. Eventually, the current review outlined significant implications that provide a strong foundation for future research.